2020
DOI: 10.1073/pnas.2001103117
|View full text |Cite
|
Sign up to set email alerts
|

A cost-effectiveness analysis of the number of samples to collect and test from a sexual assault

Abstract: Although the backlog of untested sexual assault kits in the United States is starting to be addressed, many municipalities are opting for selective testing of samples within a kit, where only the most probative samples are tested. We use data from the San Francisco Police Department Criminalistics Laboratory, which tests all samples but also collects information on the samples flagged by sexual assault forensic examiners as most probative, to build a standard machine learning model that predicts (based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…The incremental cost‐effectiveness analyses showed that investigating all cases instead of only those with CODIS hits meant paying $9121 p/additional indictment and $12,000 p/additional conviction. Given the $241,960 tangible and intangible societal cost for each sexual assault, this is a relatively small price for the system to expend to get dangerous sexual offenders [40] off the streets, give justice to victims [43], and make the community safer [40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incremental cost‐effectiveness analyses showed that investigating all cases instead of only those with CODIS hits meant paying $9121 p/additional indictment and $12,000 p/additional conviction. Given the $241,960 tangible and intangible societal cost for each sexual assault, this is a relatively small price for the system to expend to get dangerous sexual offenders [40] off the streets, give justice to victims [43], and make the community safer [40].…”
Section: Resultsmentioning
confidence: 99%
“…From a total societal cost perspective, investigating all cases led to a cost savings of $26.48 million. Investigations with CODIS hits were more cost‐effective than those without CODIS hits [43], as a larger percentage resulted in indictments and convictions. However, also investigating cases without CODIS hits was cost‐effective due to the cost savings from future sexual assaults averted, thereby providing strong support for the “investigate all” policy.…”
Section: Discussionmentioning
confidence: 99%
“…They call for further collection of cost data to be able to assess the value and associated ROI from probative use of forensic evidence. Since that call, several sources of cost and benefit data have emerged that will permit the ROI determination [ 15 , 17 , 22 , 23 , [41] , [42] , [43] , [44] ].…”
Section: Return On Investmentmentioning
confidence: 99%
“…Can we determine the impact of forensic science on the justice system? Many studies have addressed the question of the value of forensic science and the measurement of those contributions ([ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]). A fundamental component of that question involves what specific analytical outcomes signify value and how to measure each interpretation of value.…”
Section: Introductionmentioning
confidence: 99%
“…The SAK used by trained medical or forensic professionals provides all the tools necessary to safely collect and gather evidence following a sexual assault. Although the kit contents can vary between Forensic sciences; forensic toxicology; drug-facilitated; sexual assault; DFSA; chemical submission; SANE; SART REVIEW jurisdictions and municipalities [1], they typically include instructions for collection, swabs for DNA, vials for blood collection, sterile jars for urine collection, labels for evidence, bags for storage, and documentation to initiate a chain of custody [6,7]. With respect to forensic toxicology, the results of the analyses performed on collected biological specimens do not necessarily "solve" a case, but they can support the perceived credibility of the survivor [8].…”
Section: Introductionmentioning
confidence: 99%